2019
DOI: 10.7202/1065058ar
|View full text |Cite
|
Sign up to set email alerts
|

Student Writers’ Affective Engagement with Grammar-Centred Written Corrective Feedback: The Impact of (Mis)Aligned Practices and Perceptions

Abstract: This project firstly explored Iranian English as a foreign language (EFL) students’ perceptions about written corrective feedback (WCF)-related practices and preferences. Secondly, the student participants’ first language (L1; e.g., Farsi) learner identities were operationalized, especially focusing on the skill of writing, WCF, and grammar-centred WCF. Thirdly, the students’ affective engagement with WCF was scrutinized, particularly in light of L1 student identities. The participants in the study were 15 stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In L2 writing, learners' individual differences in interaction with feedback can also be attributed to their own beliefs and experiences [24]. Saeli and Cheng [8] further confirmed this. It was found that students' L2 identity is deeply affected by their L1 identity, which in turn leads to their own preferences for various feedback related to CF.…”
Section: The Impact Of Learner Agencymentioning
confidence: 74%
See 1 more Smart Citation
“…In L2 writing, learners' individual differences in interaction with feedback can also be attributed to their own beliefs and experiences [24]. Saeli and Cheng [8] further confirmed this. It was found that students' L2 identity is deeply affected by their L1 identity, which in turn leads to their own preferences for various feedback related to CF.…”
Section: The Impact Of Learner Agencymentioning
confidence: 74%
“…However, under the claim that the assessment of L2 writing should not be limited to the pursuit of grammatical accuracy [5], other studies were carried out on the effectiveness of feedback with different focuses [6]. Moreover, when exploring students' reactions to teacher feedback, it is claimed that under certain influential factors such as beliefs [7], identity, and degree of recognition to feedback [8], students' acceptability to feedback is also diverse.…”
Section: Introductionmentioning
confidence: 99%
“…The findings revealed that positive effects in this context. Saeli and Cheng (2019) discovered that learners' preferences and perceptions play a significant role in receiving feedback and then using it. Most of the students (10/15) reported that they prefer to receive unfocused CF and the amount/frequency of error correction was not disturbing them.…”
Section: Review Of Conducted Studiesmentioning
confidence: 99%
“…Their positive attitude towards written CF demonstrates that they require written CF to improve their writing ability (Chen et al, 2016). Moreover, misaligned perceptions of written CF between L2 learners and teachers are likely to have a negative impact on L2 learners' capacity to apply CF (Saeli & Cheng, 2019).…”
Section: Corrective Feedbackmentioning
confidence: 99%